The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1177/0361198120927006
|View full text |Cite
|
Sign up to set email alerts
|

Pothole Mapping and Patching Quantity Estimates using LiDAR-Based Mobile Mapping Systems

Abstract: Pavement distress or pothole mapping is important to public agencies responsible for maintaining roadways. The efficient capture of 3D point cloud data using mapping systems equipped with LiDAR eliminates the time-consuming and labor-intensive manual classification and quantity estimates. This paper proposes a methodology to map potholes along the road surface using ultra-high accuracy LiDAR units onboard a wheel-based mobile mapping system. LiDAR point clouds are processed to detect and report the location an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 17 publications
0
19
0
Order By: Relevance
“…The same datasets were also used to compare the current strategy with the one proposed by Ravi et al (18), and the detections and reported severity of the potholes were found to be similar from the two strategies, thus validating the current method. As mentioned earlier, whereas the current strategy is designed to detect potholes directly from 3D point cloud, the one developed by Ravi et al (18) relies on additional information about the vehicle trajectory during data acquisition to achieve accurate results.…”
Section: Experimental Results and Analysismentioning
confidence: 58%
See 2 more Smart Citations
“…The same datasets were also used to compare the current strategy with the one proposed by Ravi et al (18), and the detections and reported severity of the potholes were found to be similar from the two strategies, thus validating the current method. As mentioned earlier, whereas the current strategy is designed to detect potholes directly from 3D point cloud, the one developed by Ravi et al (18) relies on additional information about the vehicle trajectory during data acquisition to achieve accurate results.…”
Section: Experimental Results and Analysismentioning
confidence: 58%
“…This implies that the approach in Kang and Choi ( 17 ) cannot be applied to MMSs moving at a considerably high speeds, which are required to map large roadway networks. Ravi et al proposed an approach for pothole detection using 3D point clouds captured by mobile LiDAR mapping systems moving at 40 to 50 mph ( 18 ). Their approach was based on 2D gridding of 3D point cloud along the road followed by an iterative 3D plane fitting within each grid to identify points that are deviating from the resultant best-fitting plane.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Data collected by MLMS has been used for extracting a wide range of road features such as pavement surfaces, lane markings, road edges, traffic signs, and roadside objects. It also facilitated applications including cross-section extraction [27,28], pavement condition monitoring [17], sight distance assessment [20,21], vertical clearance evaluation [22,29], and flood modeling in urban areas [7,8]. When compared with airborne LiDAR, ground systems provide a higher horizontal accuracy owing to their smaller laser footprint size.…”
Section: Mobile Lidar For Transportation Applicationsmentioning
confidence: 99%
“…Mobile LiDAR mapping systems (MLMS) have emerged as a prominent tool for collecting high-quality, dense point clouds in an efficient manner. Previous studies reported on the use of MLMS for automated lane marking detection [13,14], road centerline extraction [15], runway grade evaluation [16], debris/pavement distress inspection [17], traffic sign extraction [18,19], and sight distance assessment [20,21]. Mapping ditches using high-resolution LiDAR can be an efficient alternative to fielding surveys for prioritizing and planning ditch maintenance.…”
Section: Introductionmentioning
confidence: 99%